The Effect of N-Acetylcysteine on Serum Malon Di Aldehyde in Chronic Hemodialysis Patients - Ali Javaherforoush Zadeh (Journal of Global Pharma Technology, 2017)
Background: Among patients with chronic kidney diseases, oxidative stress and reactive oxygen species induce inflammatory responses, which in turn, intensify uremic complications, atherosclerosis and cardiovascular events. This study assesses the effect of N-Acetylcysteine on serum Malon Di Aldehyde (MDA) level as an oxidative stress marker in patients undergoing chronic hemodialysis (HD). Methods: The study was a double blind, and randomized clinical trial which performed on sixty ESRD patients undergoing maintenance HD at the Imam hospital, Ahvaz, Iran that randomly divided in the two groups (NAC and placebo groups).Thirty patients in the NAC group were received 600 mg of NAC tablet, twice a day for six weeks and other was received placebo at the same time. At the beginning and the end of the study, blood samples were obtained prior to the initiation of the HD session for check of serum MDA levels in two groups. Results: The mean serum MDA level in the NAC group significantly decreased from 1.95±0.86 mmol/lit to 0.92±0.4 mmol/lit (p value <0.05). In the placebo group, the mean serum MDA level before and after intervention were 1.98±1.12 and 1.5±0.91 respectively and there was no significant difference between them (p value=0.899). The mean differences in NAC group and placebo group were 1.03±0.99 and 0.48±1.05 respectively (p value<0.001).Conclusion: According to the results of our study, N-Acetylcysteine decreases serum MDA level in chronic hemodialysis patients. So, oral N-Acetylcysteine supplement may be a promising therapy for decrease of serum MDA level in these patients. Keywords: N-Acetylcysteine; Hemodialysis; Malon Di Aldehyde.